2004
DOI: 10.1038/sj.npp.1300517
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation of Human Motor Cortical Neuroplasticity by D-Cycloserine

Abstract: D-Cycloserine (CYC), a partial N-methyl-D-aspartate (NMDA) agonist, has been shown to improve cognitive functions in humans. However, the neurophysiological basis of this effect is unclear so far. We studied the impact of this drug on long-lasting after-effects of transcranial direct current (tDCS)-generated motor cortical excitability shifts, as revealed by transcranial magnetic stimulation-elicited motor-evoked potentials. While anodal tDCS enhances motor cortical excitability, cathodal tDCS diminishes it. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
176
3
10

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(207 citation statements)
references
References 39 publications
7
176
3
10
Order By: Relevance
“…In the current study, participants who received DCS showed greater potentiation of the VEP following HFvS compared with participants who received placebo. This is consistent with prior findings that DCS augmented increases in motor cortex excitability following anodal transcranial direct-current stimulation in humans (37) and augmented LTP in rat hippocampus following high-frequency electrical stimulation (38,39). Our finding is also consistent with preclinical studies demonstrating that potentiation of the VEP following HFvS is NMDAR dependent (8).…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, participants who received DCS showed greater potentiation of the VEP following HFvS compared with participants who received placebo. This is consistent with prior findings that DCS augmented increases in motor cortex excitability following anodal transcranial direct-current stimulation in humans (37) and augmented LTP in rat hippocampus following high-frequency electrical stimulation (38,39). Our finding is also consistent with preclinical studies demonstrating that potentiation of the VEP following HFvS is NMDAR dependent (8).…”
Section: Discussionsupporting
confidence: 93%
“…Whereas the effects of brief stimulation lasting for a few seconds seem to be solely based on membrane potential changes, longer-lasting stimulation for a few minutes induces lasting changes in cortical excitability, which can be stable for about one hour or even longer. These neuroplastic after-effects are assumed to be caused by a change in the strength of glutamatergic synapses, are calcium-dependent [19,20] , and thus share some similarities with long-term potentiation and depression, as found in animal studies [21] .…”
Section: Physiology Of Transcranial Electrical Stimulationmentioning
confidence: 99%
“…tDCS induces plasticity by a tonic modulation of resting membrane potentials Paulus, 2000, 2001;Nitsche et al, 2003aNitsche et al, , 2008. The aftereffects of tDCS, like those of PAS, depend on NMDA receptor and calcium channel activity (Nitsche et al, 2003b(Nitsche et al, , 2004. However, contrary to PAS, which is thought to induce plasticity at somatosensory-motor cortical synapses activated by both peripheral nerve and transcranial magnetic stimulation of the motor cortex, plasticity induction by tDCS is thought not to be restricted to specific synaptic subgroups because of the completely different stimulation protocol: in tDCS, the relatively large stimulation electrodes, which deliver a continuous current flow for some minutes, are thought to affect the majority of neurons beneath the electrodes (Nitsche et al, 2007, Purpura andMcMurtry, 1965) and thus the effects are much less restricted or focal.…”
Section: Proposed Mechanisms Of Actionmentioning
confidence: 99%